Vulnerable and Grandiose Narcissism Are Differentially Associated With Ability and Trait Emotional Intelligence - Zajenkowski, Marcin; Maciantowicz, Oliwia; Szymaniak, Kinga; Urban, Paweł (Frontiers in Psychology, 2018)
We examined the association between two types of narcissism, grandiose and vulnerable, and self-reported as well as ability emotional intelligence (EI). Grandiose narcissism is characterized by high self–esteem, interpersonal dominance and a tendency to overestimate one`s capabilities, whereas vulnerable narcissism presents defensive, avoidant and hypersensitive attitude in interpersonal relations. In the current study (n = 249) we found that vulnerable narcissism was significantly and negatively associated with trait (self-reported) EI;, however it did not correlate with ability (performance) EI. Grandiose narcissism was significantly positively connected with trait EI. Moreover, when the two EI scores were analyzed together in one a single model, they predicted were associated with grandiose narcissism in opposite directions. Specifically, trait EI showed a positive relation with grandiose narcissism, while ability EI negatively predicted this type of narcissism. The latter results are consistent with previous findings showing that individuals with high level of grandiose narcissism tend to overestimate their abilities. Vulnerable narcissism is probably connected with more realistic self-perception of emotional abilities.